Effect of 8-week core training exercises on physical and physiological parameters of female handball players - Harun Genç; Ali Erdem Ciğerci; Ozan Sever (Sergii Iermakov, 2019)
Urpose: Aim of this study was to investigate the effect of 8 weeks core training program on some physiological and physical parameters of handball team’s female players. Material and Methods: Volunteers were separated two groups as CTG (training group) and CG (control group). CTG was applied core strength training 30 min sessions 8 weeks and 3 days per week additionally handball trainings. CG wasn’t applied any core training. Effects of different core training regimes were compared after eight weeks with repeated measures MANOVA for the tests. Results: Neither group demonstrated difference for body composition measurements for repeated test scores and between groups comparisons. Significant difference was found BFP (body fat percentage) parameters on CTG. Sprint, agility, SLJ (standing long jump) scores did not increase in any groups and no difference was found between groups. Significance was found in VJ (vertical jump), back and leg strength, right and left hand grip strength, flexibility, balance parameters on CTG. Also significance was found in all core parameters on CTG. Conclusions: Results indicate that core trainings were very effective on performance based features especially on strength and core stability. So these exercises should be included in the training programs of female handball players.
Keywords: Flexibility (engineering); Core (optical fiber); High-Intensity Interval Training; Trends in Health Care Research and Practice; Significant difference; Health Sciences; FOS: Mathematics; Psychology; Orthopedics and Sports Medicine; Multivariate analysis of variance; Sprint; Analysis of variance; Repeated measures design; Statistics; Public Health, Environmental and Occupational Health; Core strength; Computer science; FOS: Psychology; Physical medicine and rehabilitation; Grip strength; Telecommunications; Medicine; Core stability; Sports Science and Performance Analysis; Training Load; Strength training; Physical therapy; Mathematics; 3. Good health